Effect of dopaminergic medication on speech dysfluency in Parkinson's disease: a longitudinal study - Tykalová, Tereza; Rusz, Jan; Čmejla, Roman; Klempíř, Jiří; Růžičková, Hana; Roth, Jan; Růžička, Evžen (Journal of neural transmission (Vienna, Austria, 2015)
Although speech dysfluencies have been hypothesized to be associated with abnormal function of dopaminergic system, the effects of dopaminergic medication on speech fluency in Parkinson's disease (PD) have not been systematically studied. The aim of the present study was, therefore, to investigate the long-term effect of dopaminergic medication on speech fluency in PD. Fourteen de novo PD patients with no history of developmental stuttering and 14 age- and sex-matched healthy controls (HC) were recruited. PD subjects were examined three times; before the initiation of dopaminergic treatment and twice in following 6 years. The percentage of dysfluent words was calculated from reading passage and monolog. The amount of medication was expressed by cumulative doses of L-dopa equivalent. After 3-6 years of dopaminergic therapy, PD patients exhibited significantly more dysfluent events compared to healthy subjects as well as to their own speech performance before the introduction of dopaminergic therapy (p < 0.05). In addition, we found a strong positive correlation between the increased occurrence of dysfluent words and the total cumulative dose of L-dopa equivalent (r = 0.75, p = 0.002). Our findings indicate an adverse effect of prolonged dopaminergic therapy contributing to the development of stuttering-like dysfluencies in PD. These findings may have important implication in clinical practice, where speech fluency should be taken into account to optimize dopaminergic therapy.
Keywords: řeč; Levodopa; Speech Disorders; akustika řeči; Male; Speech; longitudinální studie; levodopa; Dopamine Agents; dopaminové látky; Adult; Aged; dospělí; mužské pohlaví; senioři; Severity of Illness Index; lidé; ženské pohlaví; Humans; poruchy řeči; Longitudinal Studies; stupeň závažnosti nemoci; Female; Parkinson Disease; Parkinsonova nemoc; lidé středního věku; Speech Acoustics; Middle Aged